2012
DOI: 10.1002/nau.21193
|View full text |Cite
|
Sign up to set email alerts
|

Obstruction enhances rho‐kinase pathway and diminishes protein kinase C pathway in carbachol‐induced calcium sensitization in contraction of α‐toxin permeabilized guinea pig detrusor smooth muscle

Abstract: Our findings provide the first evidence that BOO enhances the ROK pathway and diminishes the PKC pathway in CCh-induced Ca(2+) sensitization in contraction of permeabilized Guinea pig DSM and suggest that inhibitors of ROK might potentially relieve bladder dysfunction related to BOO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…5). This observation is consistent with the recent report that PBOO enhanced ROCK pathway and disturbed the PKC pathway (41). PDBu induced a biphasic effect on tone in control group and lowered the tone at low concentrations (1-10 nM), whereas it increased the tone at higher concentrations (30 -300 nM) as previously reported ( Fig.…”
Section: -Dmag Treatment Alleviated An Increase In Bladder Weight Asupporting
confidence: 93%
“…5). This observation is consistent with the recent report that PBOO enhanced ROCK pathway and disturbed the PKC pathway (41). PDBu induced a biphasic effect on tone in control group and lowered the tone at low concentrations (1-10 nM), whereas it increased the tone at higher concentrations (30 -300 nM) as previously reported ( Fig.…”
Section: -Dmag Treatment Alleviated An Increase In Bladder Weight Asupporting
confidence: 93%
“…Of interest, in spontaneously hypertensive rats, hydroxyfasudil treatment was recently shown to inhibit the production of growth factors (TGF‐β1 and bFGF) and IL‐6 in ventral prostates, two important components involved in the prostatic hyperplasia progression . Activation of PKC leads to phosphorylation of CPI‐17 regulatory protein, which inhibits MLCP, increasing smooth muscle contractions independently of Ca 2+ . The PKC inhibitor GF109203X significantly reduced the contractions in control and middle‐age groups, but the contractile responses to phenylephrine remained increased in middle‐aged rats, suggesting that PKC does not take part in the prostate hypercontractility in middle‐age.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports have investigated the role of ROK inhibitors in bladder function in the context of pBOO and overactivity. Studies examining the effects of pBOO on the ROK pathway have reported the overexpression of the ROK in pBOO . These studies highlight the potential use of ROK inhibitors to control OAB associated with pBOO, but also point out the role that the overexpression of the ROK might play in allowing the detrusor muscle to generate adequate force to expel the urine past the obstruction.…”
Section: Introductionmentioning
confidence: 89%
“…The underlying mechanism behind this link has not been shown, but might be related to changes in bladder wall compliance associated with the increased MLC 20 phosphorylation. In the detrusor smooth muscle from pBOO rabbit and Guinea pig, and diabetic rabbit, calcium sensitization has been shown to play a significant role in the increase in MLC 20 phosphorylation, caused by the overexpression of ROK in animal models of lower urinary tract disease . Calcium sensitization results in an increase in MLC 20 phosphorylation independent of intracellular calcium or myosin light chain kinase activity, acting predominantly through the inhibition of the MLCP, although other mechanisms can also play a role in this process .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation